D-Dimer Determination to Exclude Pulmonary Embolism: a Two-Step Approach Using Latex Assay as a Screening Tool - de Moerloose, P; Minazio, Ph; Reber, G; Perrier, A; Bounameaux, H (Thrombosis and Haemostasis, 1994)
D-dimer (DD), when measured by a quantitative enzyme-linked immunosorbent assay (ELISA), is a valuable test to exclude venous thromboembolism (VTE). However, DD ELISA technique is not appropriate for emergency use and the available agglutination latex assays are not sensitive enough to be used as an alternative to rule out the diagnosis of VTE. Latex assays could still be used as screening tests. We tested this hypothesis by comparing DD levels measured by ELISA and latex assays in 334 patients suspected of pulmonary embolism. All but one patient with a positive (DD ≥500 ng/ml) latex assay had DD levels higher than 500 ng/ml with the ELISA assay. Accordingly, ELISA technique could be restricted to patients with a negative result in latex assay. This two-step approach would have spared about 50% of ELISA in our cohort. In conclusion, our data indicate that a latex test can be used as a first diagnostic step to rule out pulmonary embolism provided a negative result is confirmed by ELISA and the performance of the latex assay used has been assessed properly.